Sweet flag (Acorus calamus L.) rhizomes chromatography column isolates potential as rich antioxidant compounds - Suci Amalia; Lili Sunarti Hasibuan; Ninit Arinda Arianti; A Ghanaim Fasya; Diana Chandra Dewi; Deva Krisna Kadarani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
the unavailability of local materials in purposing of independently manufacturing pharmaceutical products. One of plants which can be used for raw materials in the biopharmaceuticals, sweet flag (Acorus calamus L.) that is rich in bioactive compounds such as flavonoids, alkaloids, phenolic compounds, tannins, steroids, saponins, glycosides and terpenoids. Flavonoids are the majority bioactive compounds in sweet flag rhizomes, which leads this study to isolate the flavonoids to identify as antioxidant agent for biopharmaceutical products development later. This study determined the antioxidant activity of sweet flag rhizomes as its crude extract, ethyl acetate fraction, and column isolate. Decreasing range of phytochemical compounds was remained only flavonoid that was in the column isolate.Â Liquid chromatography Mass Spectrometry (LC-MS) in column isolates was identified isorhamnetin, quercetin, kaempferol, genistein, and glycitein. Additionally, this study aims the data that column isolate has the highest purity level with the least inhibitory concentration 50%Â (IC50) and the strongest antioxidant activity.Keywords: Jeringau Rhizome, Acorus calamus, Column Isolate, Flavonoids, AntioxidantsÂ